A Method for Maintaining the Stability of Range Walk Error in Photon Counting Lidar With Probability Distribution Regulator - Jiaheng Xie; Zijing Zhang; Qunsong He; Jiahuan Li; Yuan Zhao (IEEE Photonics Journal)
Photon counting Lidar applied to long-distance ranging will face the problem of the number of received photons fluctuating with target distance and reflectivity. The Poisson probability model indicates that the range walk error of the system fluctuates with the number of received photons, which deteriorates the performance of ranging. We propose a novel approach based on the probability distribution regulator with feedback mechanism to achieve small and stable range walk error by actively controlling the number of photons incident on the detector. In this method, the attenuation rate of the probability distribution regulator varies with the number of photons to ensure that the number of photons incident on the detector is a fixed value. The simulated and experimental results with the approach demonstrate that ranging accuracy is improved significantly, and the stability of the range walk error is guaranteed.